オオトウゾクカモメ ノ ナイゾウ ゾウキ ノ ケイタイ カンサツ - 雨宮, 淳三; アメミヤ, ジュンゾウ; AMEMIYA, Junzo (国立極地研究所, 1962)
P(論文) As a result of the morphological observation on the internal organs of the south pole skua as compared with domestic fowl, the following differences have been recognized. 1) The internal face of Proventiculus reveals some lengthwise wrinkles, and its volume is comparatively small. 2) M. lateralis is thin and small in shape. 3) Intestinum caecum is not so grown a sdomestic fowl. 4) The intestine of the skua is about three times the length of the body, while that of domestic fowl is about five or six times. And these constructions are recognized as one of the special features of carnivorous birds. departmental bulletin paper